Overestimation of own body weights in female university students: associations with lifestyles, weight control behaviors and depression - Kim, M.S., Daejin University, Pocheon, Republic of Korea; Lee, H.M., Daejin University, Pocheon, Republic of Korea (Nutrition research and practice, 2010)
The study aimed to analyze the lifestyles, weight control behavior, dietary habits, and depression of female university students. The subjects were 532 students from 8 universities located in 4 provinces in Korea. According to percent ideal body weight, 33 (6.4%), 181 (34.0%), 283 (53.2%), 22 (4.1%) and 13 (2.5%) were severely underweight, underweight, normal, overweight and obese, respectively, based on self-reported height and weight. As much as 64.1% and only 2.4%, respectively, overestimated and underestimated their body weight status. Six overweight subjects were excluded from overestimation group for the purpose of this study, resulting in overestimation group consisting of only underweight and normal weight subjects. Compared to those from the normal perception group, significantly more subjects from the overestimation group were currently smoking (P = 0.017) and drank more often than once a week (P = 0.015), without any significant differences in dietary habits. Despite similar BMIs, subjects who overestimated their own weight statuses had significantly higher weight dissatisfaction (P = 0.000), obesity stress (P = 0.000), obsession to lose weight (P = 0.007) and depression (P = 0.018). Also, more of them wanted to lose weight (P = 0.000), checked their body weights more often than once a week (P = 0.025) and had dieting experiences using 'reducing meal size' (P = 0.012), 'reducing snacks' (P = 0.042) and 'taking prescribed pills' (P = 0.032), and presented 'for a wider range of clothes selection' as the reason for weight loss (P = 0.039), although none was actually overweight or obese. Unlike the case with overestimating one's own weight, being overweight was associated with less drinking (P = 0.035) and exercising more often (P = 0.001) and for longer (P = 0.001) and healthier reasons for weight control (P = 0.002), despite no differences in frequency of weighing and depression. The results showed that weight overestimation, independent of weight status, is associated with risky lifestyles, weight control behaviors, and mental conditions. Preventive interventions should focus not only on obesity, but also on body weight overestimation.